2008
DOI: 10.1375/brim.9.1.14
|View full text |Cite
|
Sign up to set email alerts
|

The Westmead Post-Traumatic Amnesia Scale for Children (WPTAS-C) Aged 4 and 5 Years Old

Abstract: Assessment of posttraumatic amnesia (PTA) in young children remains problematic. This article details a version of the Westmead PTA Scale, which was adapted for use with children aged 4 and 5 years, and an evaluation of this scale with typically developing children. The Westmead PTA Scale for Children (WPTAS-C) comprises 2 orientation and 4 memory questions, including 2 items involving remembering pictures of familiar objects. Participants included 55 preschool and kindergarten children aged 4 and 5 years. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(22 reference statements)
2
1
0
Order By: Relevance
“…At pre‐school and kindergarten ages (age 5–6 years), children still lack the conceptual understanding and vocabulary to adequately describe time and space needed for the A‐WPTAS and similar tools. Our finding that irrespective of age, all children were oriented to person and could competently state their name and reason for presentation, is also consistent with previous studies …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At pre‐school and kindergarten ages (age 5–6 years), children still lack the conceptual understanding and vocabulary to adequately describe time and space needed for the A‐WPTAS and similar tools. Our finding that irrespective of age, all children were oriented to person and could competently state their name and reason for presentation, is also consistent with previous studies …”
Section: Discussionsupporting
confidence: 93%
“…Our results also suggest that failure on the A‐WPTAS is not a reliable indicator of PTA in children aged 6 years and under. Our results are consistent with previous studies examining the performance of children on other measures reliant on temporo‐spatial orientation and new memory formation . Studies examining the effect of age on the WPTAS have reported that 45% of 4 and 5 year olds failed WPTAS temporal orientation items (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Children with an ABI were eligible for recruitment to the study if they were aged between 3 and 6 years, had been discharged from inpatient subacute rehabilitation, had not yet started school, and had a moderate or severe ABI as diagnosed by a Staff Specialist using the following framework: post-traumatic amnesia (PTA, measured on the Westmead Post-Traumatic Amnesia Scale -Child, Rocca, 2008) of 1-23 h/Glasgow Coma Scale (GCS, Jennett & Bond, 1975) of 9-12; moderate injury, PTA 24 h +/GCS < 8; severe injury. The framework utilised by Kids Rehab is a clinical application of the available literature assessing brain injury severity.…”
Section: Participantsmentioning
confidence: 99%